Offshore construction contracts in the oil industry - Touze, Jean Raphael (Department of Public Law, 2024)
The search and exploration for oil resources at sea began in the 1920s on Lake Maracaibo in Venezuela and on the shores of the Caspian Sea. Since then, there has been a continuous development of research and drilling techniques. The first offshore oil well was drilled in Louisiana in 1947 at a depth of 20 meters. Today the Total-Fina-Elf group is launching the construction of the largest and most ambitious offshore complex in the world off the Angolan coast. The project, named "Girassol", aims to extract oil at a depth of 1600 meters below sea level.